Haircuts : Estimating Investor Losses in Sovereign Debt Restructurings, 1998-2005 - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper ;, 2005)
This paper estimates bond-by-bond "haircuts"-realized investor losses-in recent debt restructurings in Russia, Ukraine, Pakistan, Ecuador, Argentina, and Uruguay. We consider both external and domestic retructurings. Haircuts are computed as the percentage difference between the present values of old and new instruments, discounted at the yield prevailing immediately after the exchange. We find average haircuts ranging from 13 percent (Uruguay external exchange) to 73 percent (2005 Argentina exchange). We also find within-exchange variations in haircuts, depending on the instrument tendered. With exceptions, domestic residents do not appear to have been treated systematically better (or worse) than foreign residents.